The Enduring Impact of Borderline Personality Pathology: Risk for Threatening Life Events in Later Middle-Age - Gleason, Marci E.J. (2011)
Both neuroticism and borderline personality disorder (BPD) are associated with increased frequency of stressful life events in young adults. It is not clear, however, whether this effect extends to later life because BPD is apparently diminished in frequency and severity when people reach middle adulthood. This issue was examined in a representative, community sample of men and women between the ages of 55 and 64 (N=1,234). Ten DSM-IV PDs and neuroticism were assessed at baseline using a semi-structured interview (SIDP-IV) and questionnaire (NEO-PI-R). Life events were measured 6 months later with a self-report questionnaire (LTE-Q) followed by a telephone interview. BPD features and neuroticism predicted increased frequency of life events, based on both self and interviewer-adjusted reports of negative life events. Avoidant and paranoid PD features predicted decreased frequency of negative life events. Approximately 42% of events reported on the LTE-Q were discounted following the telephone interview; higher scores on BPD symptoms were associated with more adjustments to self-report of threatening experiences. These findings indicate that symptoms of BPD and neuroticism continue to have a harmful impact on the lives of older adults.